ANALISIS PENANGANAN CORONAVIRUS DISEASE 2019 (COVID-19) BERDASARKAN PERATURAN GUBERNUR NOMOR 27 TAHUN 2020 TENTANG PEDOMAN PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) DI KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Bakri, Ahmad; Erlinda, Sri; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:This research is motivated by the fact that there are still many cases of the spread of Coronavirus disease 2019 (Covid-19) in Indonesia, which until now has not been resolved. With the efforts of the local government, especially Kerumutan District, which directly handles the spread of Coronavirus disease 2019 (Covid-19). The formulation of the problem in this study is handling analysisCoronavirus disease 2019(Covid-19) based on Governor Regulation Number 27 of 2020 concerning Guidelines for Large-Scale Social Restrictions (PSBB) in Kerumutan District, Pelalawan Regency. The research objective is to find outhandlingCoronavirus disease 2019(Covid-19) based on Governor Regulation Number 27 of 2020 concerning Guidelines for Large-Scale Social Restrictions (PSBB) in Kerumutan District, Pelalawan Regency.Based on Governor Regulation Number 27 of 2020 concerning Guidelines for Large-Scale Social Restrictions.This research method is descriptive quantitative, data collection techniques used questionnaires (questionnaire), interviews and documentation. The research variable is Governor Regulation Number 27 of 2020 which consists of 14 indicators of 66 questions based on research instruments. The population of this research iscommunity in Kerumutan District, Pelalawan Regency. The research sample was taken using techniquespurposive sampling. The number of samples taken in this study were 111 people. Based on the results of research and recapitulation that has been done by researchers. Respondents who answered